1994
DOI: 10.1111/j.1365-2249.1994.tb06119.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible association of CD3 and CD4 polymorphisms with insulin-dependent diabetes mellitus (IDDM)

Abstract: SUMMARYPopulation and family studies show that predisposition to type I diabetes (IDDM) is multifactorial, and that polymorphisms in the MHC region contribute substantially to the susceptibility to IDDM. In the present study the association of polymorphisms in the CD4 and the 6 subunit of CD3 with IDDM were examined in a Belgian population. We observed that the frequency ofthe CD4*A4/A4 genotype and ofthe CD3*91 allele were significantly increased (i* = 00077) and decreased {P = 3'8 x 10"^), respectively, in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…The individual alleles however showed no association. This finding contrasts with the observation that a similar association was not found in IDDM but in IDDM the CD4*A4/A4 genotype showed association (Zamani Ghabanbasani et al 1994a) .…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The individual alleles however showed no association. This finding contrasts with the observation that a similar association was not found in IDDM but in IDDM the CD4*A4/A4 genotype showed association (Zamani Ghabanbasani et al 1994a) .…”
Section: Discussioncontrasting
confidence: 87%
“…In a study of insulin-dependent diabetes mellitus patients we previously found a significant association with particular CD3 and CD4 alleles (Zamani Ghabanbasani et al 1994a). In the present study the association of HLA class I1 DQAI, DQB1, DRB1, DRB3, DRB4, DRB5 and DPB1, as well as CD4 and CD3 polymorphisms were assessed in a large number of NIDDM patients.…”
mentioning
confidence: 96%
“…Subnetwork A ( Figure 5A) and B ( Figure 5B) included quite a number of previously reported T2D-related genes: Tcf4 and Dcc [32]; Cd3d [33], Uts2r [34] and Map2k1 [35]. Subnetwork C ( Figure 5C) was the largest reversed DCL-organized module and it contained an interesting four-gene-circuit (including Arpc5l, Tra1, Mcm3ap, and Hspe1) of consistent negative-topositive correlation reversal.…”
Section: Re-analyzing a T2d Dataset From The Perspective Of Differentmentioning
confidence: 74%
“…Although CD4 rs11064392 has not been investigated for its functional significance, another linked variant in promoter ( CD4 − 181C > G (rs2855534); D’=1.0 and r 2 =0.38 with rs11064392: calculated using HapMap data) was reported to affect stimulated promoter activity in vitro [21]. In addition, SNPs other than rs11064392 or a pyrimidine-rich pentanucleotide repeat polymorphism (CD4-1188 (TTTTC)) in enhancer/promoter region have been reported to be associated with autoimmune diseases (i.e., rheumatoid arthritis, systemic lupus erythematosus, and vitiligo) [22,23], multiple sclerosis that is a T-cell mediated disease of the central nervous system [24], and insulin-dependent diabetes mellitus (IDDM) [25]. It is also noteworthy that recent reports have shown that a non-synonymous SNP ( CD4 Trp240Arg), common among individuals of African descent but non-polymorphic among Caucasian, influence human immunodeficiency virus (HIV-1) infection risk [26,27].…”
Section: Discussionmentioning
confidence: 99%